Efektivitas Penerapan Non Convention Vessel Standard (NCVS) berdasarkan Peraturan Menteri Perhubungan KM.65/2009 tentang Standar Kapal Non Konvensi Berbendera Indonesia - Raihan Aradhana (Universitas Sains dan Teknologi Komputer, 2023)
The International Convention for the Safety of Life at Sea or SOLAS is basically a convention initiated by the International Maritime Organization (IMO) for the safety and security of ships at sea. However, this provision only applies to vessels measuring 500 gross tonnage and above. IMO provides flexibility to its members to apply standards for non-conventional vessels sailing in its territorial waters. Regulation of the Minister of Transportation KM.65/2009 concerning Standards for Non-Conventional Ships with Indonesian Flags is the legal basis for implementing NCVS in Indonesia. However, in practice, there are still some obstacles that the implementation has not been effective. This paper aims to measure the effectiveness of the implementation of the NCVS rules in Indonesia which were made using a juridical-normative approach. The results of this study indicate that the Government of Indonesia has not been effective enough in implementing NCVS in Indonesia by looking at several aspects, one of which is the high number of accidents of non-conventional Indonesian-flagged ships in Indonesian sea areas.